Pengenalan dan Pelatihan Sistem Pengarsipan Elektronik Berbasis Web Untuk Alumni Prodi Ilmu Perpustakaan Fakultas Ilmu Budaya Unilak - Rismayeti Rismayeti; Eko Noprianto (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2021)
This service activity aims to provide introduction and training to Alumni Ilmu Perpustakaan Fakultas Ilmu Budaya Universitas Lancang Kuning, especially those who are already working. A common problem for partners is that they do not have adequate skills in managing Web-based Electronic Archives. The implementation of this service is expected to improve the understanding and skills of Alumni Ilmu Perpustakaan Fakultas Ilmu Budaya Universitas Lancang Kuning on how to manage Web-based electronic archives. The output produced in accordance with this activity plan is in the form of scientific articles. The method of implementing the activity is counseling. Submission of material is carried out by Lecturers who are members of the team proposing online community service activities.